Epidemiological changes and financial consequences of hypertension in Latin America: implications for the health system and patients in Mexico Cambios epidemiológicos y consecuencias financieras de la hipertensión en América Latina: implicaciones para el sistema de salud y los pacientes en México - Armando Arredondo; Alexis Zuñiga (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
The aim of this study was to assess the costs and financial consequences of epidemiological changes in hypertension in México. The cost evaluation method to estimate costs was based on instrumentation techniques. To estimate the epidemiological changes and expected cases of hypertension in 2010-2012, three probabilistic models were constructed according to the Box-Jenkins technique. Comparing the economic impact, from 2010 to 2012 there will be a 24% increase in financial requirements (p < 0.05). The total cost of hypertension in 2011 will be US$ 5,733,350,291, including US$ 2,718,280,941 in direct costs and US$ 3,015,069,350 in indirect costs. If the risk factors and various healthcare models remain unaltered in the institutions analyzed here, the financial consequences will have a major impact on users' pockets, followed by social security providers and public healthcare providers. The authors suggest a revision in the planning, organization, and allocation of resources, particularly programs for health promotion and prevention of hypertension. El objetivo fue identificar los costos y las consecuencias financieras de cambios epidemiológicos referentes a la hipertensión en México. El método de evaluación de los costos, para estimar los costos directos e indirectos, se basó en técnicas de instrumentación y de consenso. Para estimar los cambios epidemiológicos y de casos esperados para el período 2010-2012, tres modelos probabilísticos se construyeron de acuerdo a la técnica de Box-Jenkins. Al comparar el impacto económico en el 2010 frente a 2012 (p < 0.05), hay un incremento del 24% de las necesidades financieras. El importe total para la hipertensión en 2011 será de US$ 5.733.350.291. Se incluyen US$ 2.718.280.941 en costos directos y US$ 3.015.069.350 en costos indirectos. Si los factores de riesgo y los modelos de atención a la salud permanecen sin cambios, las consecuencias financieras serían de mayor impacto para los bolsillos de los usuarios, siguiendo en orden de importancia, los proveedores de seguridad social y los proveedores de asistencia pública.